ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA PADA MATERI SUDUT - Hasna’ul Badiyah; Lale Amanda Fairuz; Firda Solihan; Bunga Sukma; Djuita Hidayati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT This study was motivated by the importance of mathematical connection skills in helping students understand the relationships among mathematical concepts and their application in daily life, particularly in angle material at the elementary school level. The study aimed to analyze students’ mathematical connection abilities and identify the difficulties experienced by students in relating angle concepts to other mathematical concepts and real-life contexts. This research employed a qualitative approach with an exploratory case study design involving fifth-grade students of SDN 4 Batu Layar Barat and teachers as additional informants. Data were collected through semi-structured interviews, direct observation, and documentation of students’ worksheets. Data analysis was conducted through the stages of data collection, organization, classification, interpretation, and conclusion drawing. The results showed that students’ mathematical connection abilities were still relatively low. The difficulties experienced by students included relating angle concepts to other mathematical concepts, applying angle concepts in everyday life, and transforming angle representations into symbols, images, and verbal descriptions. These difficulties were influenced by inadequate mastery of basic concepts, limited understanding of problem instructions, and lack of contextual learning experiences. Therefore, contextual, integrated, and concrete experience-based learning strategies are needed to improve students’ mathematical connection abilities. ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya kemampuan koneksi matematis dalam membantu siswa memahami hubungan antar konsep matematika dan penerapannya dalam kehidupan sehari-hari, khususnya pada materi sudut di sekolah dasar. Penelitian ini bertujuan untuk menganalisis kemampuan koneksi matematis siswa serta mengidentifikasi kesulitan yang dialami siswa dalam menghubungkan konsep sudut dengan konsep matematika lainnya maupun konteks nyata. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus eksploratoris yang melibatkan siswa kelas V SDN 4 Batu Layar Barat dan guru sebagai informan tambahan. Data dikumpulkan melalui wawancara semi-terstruktur, observasi langsung, dan dokumentasi lembar kerja siswa. Analisis data dilakukan melalui tahapan pengumpulan, penyusunan, pengelompokan, penafsiran, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kemampuan koneksi matematis siswa masih tergolong rendah. Kesulitan yang dialami siswa meliputi kemampuan mengaitkan konsep sudut dengan konsep matematika lain, mengaplikasikan konsep sudut dalam kehidupan sehari-hari, serta mentransformasikan representasi sudut dalam bentuk simbol, gambar, dan deskripsi verbal. Kesulitan tersebut dipengaruhi oleh penguasaan konsep dasar yang belum memadai, keterbatasan dalam memahami soal, dan minimnya pengalaman belajar kontekstual. Oleh karena itu, diperlukan strategi pembelajaran yang kontekstual, terintegrasi, dan berbasis pengalaman konkret untuk meningkatkan kemampuan koneksi matematis siswa.